Analisis Pendidikan Karakter Anak dalam Film Keluarga Cemara - Desty Survia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2022)
Abstract Film is one of the literary works which also as mass media that contains moral value for people indirectly affect to people’s thought and behavior. Fil is also one of an effective communication media to convey message through dialog and scene. Therefore, writer made a film as a research subject. This research is discussed about Keluarga Cemara Film especially education of children character in this film. Family trough parents ‘role able to help build a good character of children. In development era, people demanded not only smart in intellectual but also has good character. Character is particular personality as a driver and activator to distinguish one individual. This research aimed to analyze and recognize the education character of children in family. The research method used was qualitative descriptive. This research used technique sampling data to see and note dialog and scene in this film which describe or contain education character of children